The Magnolia Story - Gaines, Chip; Gaines, Joanna; Gaines, Joanna; Dagostino, Mark; Dagostino, Mark (Nashville, Tennessee : W Publishing Group, 2016)
The first book from Fixer Upper hosts Chip and Joanna Gaines, offering their fans a detailed look at their life together--from the very first renovation project they ever tackled together to the project that nearly cost them everything, from the childhood memories that shaped them to the twists and turns that led them to the life they share on the farm today.
The first book from Fixer Upper hosts Chip and Joanna Gaines, offering their fans a detailed look at their life together--from the very first renovation project they ever tackled together to the project that nearly cost them everything, from the childhood memories that shaped them to the twists and turns that led them to the life they share on the farm today.
Keywords: Gaines, Chip; Gaines, Chip; Gaines, Joanna; Gaines, Joanna; Interior decorators; Interior decorators -- Biography; Biography -- United States; United States; Designers; Designers -- Biography; Biography -- United States; United States; Architects and builders; Architects and builders -- Biography; Biography -- United States; United States; Contractors; Contractors -- Biography; Biography -- United States; United States; Television personalities; Television personalities -- Biography; Biography -- United States; United States; Dwellings; Dwellings -- Remodeling; Remodeling; Dwellings; Dwellings -- Maintenance and repair; Maintenance and repair; Autobiographies; Autobiographies